Individual difference on reading ability tested by eye-tracking: from perspective of gender. Issue 3 (4th March 2020) - Zhan, Zehui; Wu, Jun; Mei, Hu; Wu, Qianyi; Fong, Patrick S.W.
Abstract : Purpose: This paper aims to investigate the individual difference on digital reading, by examining the eye-tracking records of male and female readers with different reading ability (including their pupil size, blink rate, fixation rate, fixation duration, saccade rate, saccade duration, saccade amplitude and regression rate). Design/methodology/approach: A total of 74 participants were selected according to 6, 520 undergraduate students' university entrance exam scores and the follow-up reading assessments. Half of them are men and half are women, with the top 3% good readers and the bottom 3% poor readers, from different disciplines. Findings: Results indicated that the major gender differences on reading abilities were indicated by saccade duration, regression rate and blink rate. The major effects on reading ability have a larger effect size than the major effect on gender. Among all the indicators that have been examined, blink rate and regression rates are the most sensitive to the gender attribute, while the fixation rate and saccade amplitude showed the least sensitiveness. Originality/value: This finding could be helpful for user modeling with eye-tracking data in intelligent tutoring systems, where necessary adjustments might be needed according to users' individual differences. In this way, instructors could be able to provide purposeful guidance according to what the learners had seen and personalized the experience of digital reading.